Educational Innovation from Distributed Leadership: Case Study Spanish Public School - García, Ingrid (2017)
The purpose of the communication is to present a case study of distributed leadership practices and the performances of the Principal of a public school in Madrid. Educational leadership can be considered one of the most important elements of the education system to be effective, achieve quality results, develop processes of change and improvement. As a case study, in which the Principal of the public and bilingual school of the Community of Madrid, Spain, cooperated. The qualitative cut methodology was used with a descriptive and interpretative approach, the structured interview in depth was an instrument of data collection. The main objective is to describe, through a case study: How are the practices of DL and actions of the Principal of a public school exercised? The results found are very broad. The dimensions of the DL are four: DL Practices, Shared Decisions, Mission and Vision, Professional Development.